INVESTIGASI EMPIRIS TRANSFORMASI DIGITAL DAN EFEKTIVITAS TATA KELOLA ELEKTRONIK (E-GOVERNANCE) DI SEKTOR PUBLIK MALAYSIA - Umar Abdullahi; Prof. Halimah Abdul Manaf (Post Graduate School of Government Science, 2025)
This study investigates the relationship between digital transformation and e-governance effectiveness in Malaysia’s public sector, employing an integrated model based on the Technology–Organization–Environment (TOE) framework and the Unified Theory of Acceptance and Use of Technology (UTAUT). Despite Malaysia’s progressive digital initiatives under the MyDIGITAL Blueprint and the Public Sector Digitalisation Strategic Plan (2021–2025), variations persist in the implementation and utilization of e-government systems across ministries and agencies. Using a quantitative research design, data were collected from 354 civil servants across federal and state institutions in Putrajaya, Kuala Lumpur, and Selangor. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to examine the effects of technological readiness, organizational capability, environmental policy support, performance expectancy, and facilitating conditions on e-governance effectiveness. The results reveal that all five constructs significantly influence e-governance effectiveness, explaining 68.1% of its variance. Among these, organizational capability emerged as the strongest predictor, followed by environmental policy support and facilitating conditions. The findings highlight that the success of digital transformation in Malaysia’s public sector depends not only on technological infrastructure but also on institutional readiness, supportive policy environments, and user acceptance. The study contributes theoretically by empirically validating an integrated TOE–UTAUT model in a developing-country public sector context and offers practical insights for strengthening interoperability, capacity building, and citizen-centric digital service delivery.